Determinants of Zakat Payment Behavior through Digital Platforms in Makassar City - K, M Yusuf; Parmitasari, Rika Dwi Ayu; Haddade, Abdul Wahid (Jurnal Ar-Ribh, 2023)
This study aims to examine the factors that determine muzakki behavior in paying zakat through digital platform services in the city of Makassar. The type of research used is applied research with field studies. The approach used in this research is quantitative with causal associative. The method in this study is through primary data collection by distributing questionnaires and secondary data through data collection at BAZNAS and LAZ in Makassar City as well as through reference journals related to the study title. The sample technique used is the Ferdinand formula with a sample size of 332. The data analysis technique used in this study is the Structural Equation Model (SEM). The results of this study show that the perception of usefulness has a significant effect on the intention of muzakki, the perception of ease of use has a significant effect on the intention of muzakki, digital knowledge has a significant effect on the intention of muzakki, the perception of usefulness does not affect the behavior of muzakki, simple perception. usage has a significant effect on muzakki behavior, digital knowledge has a significant effect on muzakki behavior, intention has a significant effect on muzakki behavior, perception of usefulness has a significant effect on behavior through muzakki intention, perception of ease of use has a significant effect significant on behavior through muzakki intention and digital knowledge has a significant effect on behavior through muzakki intention